A histological study of the alimentary canal and associated structures in the adult of the stem borer Sesamia Calamistis Hmpsn. (Lepidoptera : noctuidae) - Le Grice, D. S.(David Stanley) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1967.